IMPACT OF AGRIBUSINESS ENTREPRENEURIAL TRAINING ON ENTREPRENEURIAL ATTITUDES AMONG STUDENTS OF OYO STATE COLLEGE OF AGRICULTURE AND TECHNOLOGY, IGBOORA, OYO STATE, NIGERIA. - Oyeronke A Adekola; Ajibola Abdulrahamon Ishola (Agricultural Socio-Economics Journal, 2020)
The study explores the impact of Agribusiness entrepreneurial training on entrepreneurial attitudes among students of Oyo State College of Agriculture and Technology (OYSCATECH), Igboora. The study was a cross-sectional design. 132 students offering entrepreneurship education in Agriculture were sampled using a self-report questionnaire and multi-stage sampling. The larger percentage (88.6%) of the respondents were below the age of 25 years, studying Science, management, agriculture engineering and Agriculture management based courses. 52.3% were females and 47.7% were males. Data was analysed using descriptive statistics, Pearson correlation analysis and multiple regression analysis at p≤0.05.Results reveals that students benefitted from vocation training such as fish production (93.2%); Egg/Broiler production (92.4%), Fish hatchery management (93.9%), Piggery/Rabbit production (93.9%), Fish processing and value addition (92.4%) and Grain/crop production (90.9%). The entrepreneurship skills benefitted include business start-ups (85.6%), managerial coordination (92.4%), book keeping and accounting, (84.8%) among others. Entrepreneurship skills acquired, its perceived adequacy and value correlated significantly with entrepreneurship attitudes. Entrepreneurship skills acquired and its perceived value were significant predictors of attitude towards entrepreneurship while the role of adequacy of entrepreneurship skills was negligible.It was concluded that Agricultural entrepreneurship skills acquired and its perceived value were factors motivating entrepreneurship attitude among students